2019
DOI: 10.1080/17458080.2018.1502479
|View full text |Cite
|
Sign up to set email alerts
|

A pilot toxicology study of biogenic silver nanoparticles: in vivo by intraperitoneal and intravenous infusion routes in rats

Abstract: Toxic effects of nanoparticles on human health are considerably increasing their worldwide recognition. Currently silver nanoparticles are being widely used in consumer medical products, due to its uniqueness in biomedical applications. Uptake of these particles via various administration routes can also lead to different toxic effects. In this study, we assessed the toxic effect of 11-75 nm ranged biogenic silver nanoparticles (Bio-AgNPs) on male wistar rats by using two different administration routes namely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The significant impact of AgNPs size on their biological activity has been reported by many authors [243,247,248]. Ashajyothi and Chandrakanth [240] studied animal toxicity using 11-75 nm biogenic AgNPs (bio-AgNPs) in the male Wistar rat. It was also reported that the cytotoxicity of bio-AgNPs against normal and cancer cell lines is dose-dependent.…”
Section: Toxicity Of Biogenic Agnpsmentioning
confidence: 94%
See 2 more Smart Citations
“…The significant impact of AgNPs size on their biological activity has been reported by many authors [243,247,248]. Ashajyothi and Chandrakanth [240] studied animal toxicity using 11-75 nm biogenic AgNPs (bio-AgNPs) in the male Wistar rat. It was also reported that the cytotoxicity of bio-AgNPs against normal and cancer cell lines is dose-dependent.…”
Section: Toxicity Of Biogenic Agnpsmentioning
confidence: 94%
“…In contrast, few studies on the patterns of NPs transport, accumulation, degradation, and elimination using animal models have been performed [55]. For this reason, in recent years, the number of nanotoxicology studies that have investigated the biological pathways affected by nanoparticles and induced toxic effects has increased substantially [240]. There is no doubt that deeper knowledge of the mechanisms of bio-AgNPs' effect on living organisms will discover new areas of their application in the near future.…”
Section: Toxicity Of Biogenic Agnpsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Ashajyothi, C et al, 11–75 nm size biogenic AgNPs can be excreted from the body by the kidneys without causing any harm. 74 Conversely, 10 nm-size particles are deleterious for the kidneys. 70 On the other hand, microscopic observation of heart tissue revealed no sign of congestion of heart muscle, extravasation of RBCs, muscle fascicles, and infiltration of immune cells in treatment groups ( Figure S6 ).…”
Section: Resultsmentioning
confidence: 99%
“…This confirms normal renal function of the treatment groups. According to Ashajyothi, C et al, 11–75 nm size biogenic AgNPs can be excreted from the body by the kidneys without causing any harm . Conversely, 10 nm-size particles are deleterious for the kidneys .…”
Section: Resultsmentioning
confidence: 99%